Methylation-dependent DNA Restriction in Bacillus anthracis - Sitaraman, Ramakrishnan (2011)
Bacillus anthracis, the causative agent of anthrax, is poorly transformed with DNA that is methylated on adenine or cytosine. Here we characterize three genetic loci encoding type IV methylation-dependent restriction enzymes that target DNA containing C5-methylcytosine (m5C). Strains in which these genes were inactivated, either singly or collectively, showed increased transformation by methylated DNA. Additionally, a triple mutant with an ~30-kb genomic deletion could be transformed by DNA obtained from Dam(+)Dcm(+) E. coli, although at a low frequency of ~10(−3) transformants/10(6) cfu. This strain of B. anthracis can potentially serve as a preferred host for shuttle vectors that express recombinant proteins, including proteins to be used in vaccines. The gene(s) responsible for the restriction of m6A-containing DNA in B. anthracis remain unidentified, and we suggest that poor transformation by such DNA could in part be a consequence of the inefficient replication of hemimethylated DNA in B. anthracis.